2021
DOI: 10.3390/cancers13030443
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Mesenteric Mass in Small Intestinal Neuroendocrine Tumours

Abstract: Background: A metastatic mesenteric mass is a hallmark of small intestinal neuroendocrine tumours (SI-NETs). However, little is known on its development over time. Therefore, we conducted a study to assess the evolution of a SI-NET-associated mesenteric mass over time. Methods: Retrospectively, 530 patients with proven SI-NET were included. The presence and growth of a mesenteric mass was assessed using RECIST 1.1 criteria on every consecutive CT-scan until the end of follow-up or resection. Results: At baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…This may suggest that the mesentery is more sensitive to differences in sex hormone levels than other organs, making the protective effects of ERα signaling on SI-NET metastasis most noticeable in the mesentery. In previous research, we showed that men have a higher risk of mesenteric metastases growth compared to women ( 3 ). The gradual increase in prevalence of mesenteric metastases over the years in women, instead of a sharp increase after menopause shown in this study, may be explained by the very slow growth rate of mesenteric metastases ( 3 ).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This may suggest that the mesentery is more sensitive to differences in sex hormone levels than other organs, making the protective effects of ERα signaling on SI-NET metastasis most noticeable in the mesentery. In previous research, we showed that men have a higher risk of mesenteric metastases growth compared to women ( 3 ). The gradual increase in prevalence of mesenteric metastases over the years in women, instead of a sharp increase after menopause shown in this study, may be explained by the very slow growth rate of mesenteric metastases ( 3 ).…”
Section: Discussionmentioning
confidence: 84%
“…In previous research, we showed that men have a higher risk of mesenteric metastases growth compared to women ( 3 ). The gradual increase in prevalence of mesenteric metastases over the years in women, instead of a sharp increase after menopause shown in this study, may be explained by the very slow growth rate of mesenteric metastases ( 3 ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Importantly, PRRT is not effective in decreasing the size of mesenteric masses in SB-NETs and is likely not beneficial in treating bowel complications. 79…”
Section: Limitations and Challengesmentioning
confidence: 99%
“…Importantly, PRRT is not effective in decreasing the size of mesenteric masses in SB-NETs and is likely not beneficial in treating bowel complications. 79 One last issue relates to patients with poor performance status (PS). Anecdotally, patients can have poor outcomes from PRRT if they have a poor baseline PS, and poor PS has been shown to be an independent prognostic factor for OS after PRRT.…”
Section: Limitations and Challengesmentioning
confidence: 99%